Emerging Voices : Experiences of Underrepresented Asian Americans - Ling, Huping, 1956- (Book collections on Project MUSE., 2008)
While a growing number of popular and scholarly works focus on Asian Americans, most are devoted to the experiences of larger groups such as Chinese, Japanese, Korean, Filipino, and Indian Americans. As the field grows, there is a pressing need to understand the smaller and more recent immigrant communities. Emerging Voices fills this gap with its unique and compelling discussion of underrepresented groups, including Burmese, Indonesian, Mong, Hmong, Nepalese, Romani, Tibetan, and Thai Americans. Unlike the earlier and larger groups of Asian immigrants to America, many of whom made the choice.